Coping and coping assistance among children with sickle cell disease and their parents - Hildenbrand, Aimee K. (2015)
The ways in which a family copes with the physical and psychosocial burdens of sickle cell disease (SCD) can influence child and family functioning. However, few studies have examined SCD-related stressors beyond pain or how children and parents cope with these stressors. This study aimed to describe child coping and parent attempts to help their children cope (i.e., coping assistance) with a range of SCD stressors by using a triangulated mixed methods design. We also explored convergence between findings from qualitative interviews and quantitative coping inventories. Fifteen children (aged 6 – 14) with SCD and their parents (N = 15) completed semi-structured interviews and self-report measures to assess SCD-related stressors, coping, and coping assistance strategies. Findings indicate that children experience numerous stressors related to SCD and its treatment, including but not limited to pain. To manage these stressors, families employ a range of approach- and avoidance-oriented coping strategies. Quantitative and qualitative assessments provided complementary and unique contributions to understanding coping processes among children with SCD and their parents. Examining a broad range of stressors and integrating multiple assessment methods helps improve our understanding of coping with pediatric SCD, which may inform clinical practice and family-focused intervention development.